Pendidikan Kesehatan Terhadap Tingkat Kemandirian Keluarga Dalam Merawat Penderita TB di Wilayah Kerja Puskesmas Lembang - Muh Fauzar Al-Hijrah; Muhammad irwan; Rika Kurnia Kandacong; Sherly (Yayasan Literasi Sains Indonesia, 2022)
In 2014, the highest number of cases of pulmonary TB were in Africa (37%), Southeast Asia (28%), and the Eastern Mediterranean region (17%). In West Sulawesi (2016) the number of new cases of positive and active BTA pulmonary TB as many as 1,240 patients, the most cases are men, namely, 771 (62%) while women 469 (38%). BTA positive pulmonary tuberculosis coverage is cured, complete treatment, and treatment success rate by province in 2016, treatment success 1,077 with successful treatment as much as 84.8. This study aims to find out the relationship of health education to the level of family independence in caring for tb sufferers. The type of research used is observational analytical research using cross sectional research designs. The research was conducted in the Lembang Majene Health Center Work area. A sample of 33 people. Fisher's Exact Test result was obtained a value of P = 0.000 (<0.05). Then it can be concluded that there is a relationship between knowledge and the level of family independence in caring for TB sufferers. It is expected to puskesmas officers to socialize home care nursing (home visits) and further improve the quality of service to people with Pulmonary TB, especially in terms of drug taking schedules.